Disability rights are protected under Law No. 8 of 2016: The Right to Be Free from Legal Discrimination Against Persons with Disabilities - Siregar, Dahris; Mentari, Juwita; Dewi, Dahlia Kusuma; Darma, Mospa (Universitas Pahlawan Tuanku Tambusai, 2024)
People who experience physical limitations, such as not being able to see or walk, having below-average general intelligence, or being mentally retarded for a long time are called people with disabilities. Disabled individuals, both young and old, face so many difficulties that hinder their development and well-being, that it is very difficult for them to maximize their abilities and achievements. Regulation No. 18 of 2016 on Persons with Disabilities is one of many laws that have been enacted in an effort to obtain rights and stop the prejudice towards people with impairments. The study's main focus is on the legal protection against discrimination against individuals with disabilities provided by Law No. 18 of 2016 concerning Persons with Disabilities, as well as the rights to be free from discrimination against them. Normative juridical research methodology is used. Studies show that inclusive education provided by governments can help people with disabilities understand their right not to be discriminated against.